Appropriate Learning Methods for Autistic Children in Improving Tooth brushing Skills: a Review - Sunomo Hadi; Mega Djuliawanti; Agus Marjianto; Jumriani Jumriani (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2022)
Autistic children have poor oral hygiene levels higher than normal children. Dental and oral health problems that often occur in children with autism are the risk of dental caries which is higher than other dental and oral diseases. Frequent consumption of cariogenic foods and impaired coordination of the tongue muscles result in a tendency to eat food and difficulty swallowing, resulting in the formation of debris. The high value of debris causes calculus and if left further it will develop into worse tooth and gum damage. Objective: To describe appropriate learning methods for children with autism in improving their brushing skills. Methods: Search journals for 2016-2021 on Google Scholar, Pubmed, and Sciendirect databases. In the 8 journals used, 4 of them used quantitative research methods, 2 used prospective research methods, and 2 others used cross-sectional research methods. Results: The various methods obtained are the use of the PECS method; Yoga Therapy; iPads; Social Stories, TEACCH method, Puzzle Series; and Videos. Several kinds of learning methods are appropriate and can be recommended for children with autism, namely the video learning method which is considered better and can attract the attention of children with autism in improving their brushing skills.